DNV Case Studies - Aled Jones; Felicity Clarke (Anglia Ruskin University, 2020)
Three case studies from the Debating Nature's Value network exploring the use of monetisation in Natural Capital decision making.
Ely
In June 2019, we visited an Open Farm day near Ely in
Cambridge, to ask attendees their views on the concept of “monetising nature”.
They also expressed their ideas on ways to protect their local environment for
future generations. Many spoke of their enjoyment of accessing local natural
spaces, from parks to woodlands, and felt that it had value to them and their
families. Several spoke of the cost of accessing privately managed spaces, and
felt there was a duty to keep nature open to all. The question of how nature as
a public good should be funded was discussed, many didn’t want to see a raise
in taxation, but a reallocation of existing resource and investment to keeping
green spaces accessible.
Wensum
Dr Iain Robinson, a landowner from Wensum Valley, and Andrew
Boswell, Environmental consultant, discuss the proposed Norwich Western Link
Road, and the ecological, financial and climate impacts of such a proposal. They explain the importance of the semi-managed mature
woodland environments for biodiversity, and how they cannot be replaced by the
creation of woodlands and wetlands elsewhere, as part of the plan for ‘net
gain’. They state that new habitat creation will lack the complexity achieved
by hundreds of years of organic development as woodland matures, making the
concept of net gain void, and the project indefensible.
Felixstowe
Victor Anderson, from Anglia Ruskin University, talks
to Andrew Excell from Wildlife Trust, at the site of Trimley Marshes Nature
Reserve, which was created in 1989 in response to a project to expand, and
increase international trading operations of, Felixstowe Docks. Andrew explains
how impact on the Estuary System, which is a Specially Protected Area, was
mitigated by these 200 acres to create the Nature Reserve. In response to Victor’s question, Andrew
explains that it’s not a replacement, but a strategic and acceptable
compromise, to continue to support around 60,000 birds each winter, and year
round habitat.
Keywords: Philosophy